A Comparative Study of the Physio-Mechanical Properties of Iron Fillings and Mild Steel Chips in Reinforced Particleboard - Gandhi, Surjit Kumar; Lal, Harmesh; Chaurasiya, Shailendra Kumar; Arif, Mohammad (Journal of Advanced Research in Mechanical Engineering and Technology, 2026)
This study compared the physio-mechanical characteristics of mild steel chips and iron fillings on sawdust-produced particleboard to regular particleboard made from sawdust alone, using identical production conditions. Particle board was made using 1.18mm sawdust, 3mm mild steel chips, and iron filler with diameters of 0.15mm, 0.425mm, 0.6mm, 1.18mm, and 2.0mm. 70g of sawdust, 40g of iron filings, and 40g of mild steel chips were used in the production process. 50 ml urea formaldehyde was used as a binder. The atomic absorption spectroscopy was determined for iron filings and mild steel chips. Particleboards were produced at a temperature of 160°C and a pressure of 20 tonnes for 15 minutes. The mechanical property tested indicates that particleboard containing iron filings has a lower MOR because the size of the iron filings in the particleboard reduces as the MOR increases. The particle size of iron filling with the value of 2.0 mm had the least MOR of 3.99 MPa/m² in iron filling samples. The MOR of mild steel chips was higher compared to all the samples analysed. The MOE of particleboard produced from iron filings increases as the particle sizes of iron filings increase. The samples containing iron filings alone showed the highest MOE of 244.89 MPa/m² for 2.0 mm particle board, while the ones containing mild steel chips had the highest MOE of 282.82 MPa/m² across all samples, suggesting their strength as reinforcement. The rate of water absorption and thickness of swell of particleboard produced from iron filings increases as the size of the iron filings increases. DOI: https://doi.org/10.24321/2454.8650.202502